(untitled) (Agriculture, Food, and Natural Resources Journal, 2025)
This study evaluates the insecticidal effects of two plant powders, Piper guineense and Aframomum melegueta, on the mortality and emergence of Callosobruchus maculatus, a significant pest of stored beans. Using a completely randomized design (CRD), different concentrations (0 g, 5 g, 10 g, 15 g, and 20 g) of the plant powders were applied to 100 g samples of black-eyed peas. Mortality rates were recorded daily for seven days. Data collected was subjected to descriptive statistics and analysis of variance. Piper guineense exhibited a remarkable insecticidal effect, achieving 100% mortality across all concentrations by Day 6. In contrast, Aframomum melegueta showed a more gradual effect, with the highest concentration (20 g) reaching only 93.33% mortality by Day 7. Additionally, P. guineense completely suppressed the emergence of adult weevils at 5 g and 15 g concentrations, while A. melegueta achieved only moderate suppression at higher concentrations. Piper guineense recorded higher average mortality at 15 g (73.33%) and 20 g (67.62%) compared to A. melegueta (57.14% and 56.67%, respectively), though these differences were not statistically significant (p > 0.05). Notably, P. guineense completely suppressed adult weevil emergence at some concentrations, highlighting its practical potential as a natural insecticide for managing C. maculatus in stored beans and supporting its use in sustainable pest control strategies.